Pengaruh Kepemimpinan dan Motivasi Kerja Terhadap Disiplin Kerja Pegawai pada Kantor Inspektorat Daerah Kabupaten Karanganyar - Umi Latifah, Vina; Sutarno (Teewan Journal Solutions, 2025)
The State Civil Apparatus (ASN) is the front guard in carrying out government-based community services so that employee work discipline behavior must be considered in order to obtain satisfactory work results. The Karanganyar Regency Regional Inspectorate work unit is one of the agencies experiencing employee work discipline problems which in pre-survey research is thought to be influenced by leadership and work motivation. The aim of this research is to analyze the significant influence of leadership and work motivation on employee work discipline. The population in this study was 57 employees. The number of samples used was 50 ASN people who worked at the Karanganyar Regency Regional Inspectorate Office. The data collection technique uses a questionnaire. Data analysis techniques use validity tests, reliability tests, classical assumption tests, descriptive analysis, multiple linear regression analysis, t test, F test and coefficient of determination test. Testing the research instrument obtained that the questionnaire items on all variables were valid and reliable. The classical assumption test shows that all variables pass the classical assumption test. Multiple linear regression analysis showed that leadership had a positive influence and work motivation had a positive influence with the equation Y= -0.689 + 0.299X1 + 1.148X2 + e. Hypothesis testing showed that leadership had a significant effect on employee work discipline at the Karanganyar Regency Regional Inspectorate Office, while work motivation had a significant effect on employee work discipline at the Karanganyar Regency Regional Inspectorate Office. The F test for model accuracy shows that the research model used is appropriate. The coefficient of determination test shows that the ability of the leadership and work motivation variables to explain the influence on employee work discipline is 71.9%.